Orbitofacial Anthropometry in a Pakistani Population - Mazhar-ul-Hassan, Saba Alkhairy, Farnaz Siddiqui (Pakistan Journal of Ophthalmology, 2016)
Purpose: To demonstrate the anthropometric variations in head circumference, inner and outer canthal distances and interpupillary distance in Pakistani population. Study Design: Cross sectional study. Place and Duration of study: The data was collected for a period of three months from August 2015 to October 2015 at the OPD of the Dow University of Health Science, Dow International Medical College, Karachi, Pakistan. Material and Methods: A total of 500 patients were recruited from an Outpatient Ophthalmology department of Dow University of Health Science, Dow International Medical University. ICD(inter canthal distance) was measured between the medial angles of the palpebral fissures and the OCD(outer canthal distance) from the lateral canthus of each eye using a metal rule .The head circumference was measured using an inch tape and the IPD(inter pupillary distance) was measured using an autorefractrometer. Each of the measurements were done twice to the nearest 0.5 mm by two different researchers and an average was taken of these two measurements. Results: Total 500 subjects were used. Males were 227 (45.4%) and female were little more 273 (54.6%). The mean values for the parameters measured are as following: Head Circumference (Mean: 55.0cm ± 1.8cm), Inner canthal distance (Mean: 3.4cm ± 0.4cm), Outer canthal distance (Mean: 10.7cm ± 3.9cm), Inter pupillary distance (Mean: 61.4mm ± 4.3mm). Overall there is no mean difference found by gender or age group separately except difference in age groups for Inter pupillary distance. Conclusion: This study shows that anthropometric variations for head circumference, inner canthal distance, outer canthal distance and the interpupillary distance are seen with age and gender. Standard baseline values should be defined for these parameters and these should be considered when classifying a patient with hypertelorism, hypotelorism or telecanthus or when planning an orbital surgery. Keywords: Anthropometry, inner canthal distance (ICD), outer canthal distance (OCD), interpupillary distance (IPD) and head circumference (HC).